"A gente é muito maior, a gente é um corpo coletivo" : produções de si e de mundo a partir da ancestralidade, afetividade e intelectualidade de mulheres negras lésbicas e bissexuais - Paula Rita Bacellar Gonzaga (2019)
The experiences of black women from the colonial civilization framework are crossed by powerful fictions that reiterate the subordination, bestialization and domestication of this group. The erasure of these women by ethnocentrism, epistemicide, racism, when tis aggravated when they assert themselves lesbian and bisexual, entering the field of social movements that resist addressing race and sexuality in an intersectional way. Constituted as the Other of masculinity, whiteness and compulsory heterosexuality, lesbian and bisexual black women have produced challenges and propositions of new modes of political organization, of experiencing affection and of valuing and preserving ancestry. The purpose of this thesis is to analyze the self productions that these black women are creating from the fissures of the modern/colonial gender system. The specific objectives were: mapping the intersections of the modern / colonial gender system in the narratives highlighting its reverberations in the production of mental suffering; understanding how the search for ancestry of the black population, especially the rapprochement with religions of African origin, reverberates in the resignification of the meaning of their existence; Reflecting on the decolonization strategies of black women regarding the experiences of affection and sexuality, understanding the experience of affective relationships as a potent humanity sign humanity that they build for themselves and; knowing the propositions of epistemic, artistic, political, aesthetic and social revolutions that the interlocutors have produced from the processes of decolonization of themselves and the world. The narratives were produced in twelve methodological meetings with black women, among which nine affirm themselves as lesbians and three as bisexuals, from Brasilia, Pernambuco, Bahia and Minas Gerais. They were identified with fictitious names: Aqualtune, Audre, Hope, Iyá Adetá, Lélia, Luiza, Na Agotimé, Neusa, Nieves, Teresa, Zacimba and Zeferina to ensure confidentiality. The methodology of the meeting bets on an abebenic effect, where interlocutors and researcherrepresent subjects from the same historical continuity, regarding race, gender, class, generation and sexuality, structural markers of the modern / colonial gender system. From the interpellations of these women, it is possible to conclude on the urgency of addressing mental suffering as a product of the abjection imposed on individuals who represent historically dehumanized groups; the need to understand race as the backbone that articulates other identity markers and reverberates in the affective and intellectual experience of black women; the absence of productions about the existence of black lesbians and the complexities and potentialities of the articulation between women through affection, as well as the centrality of ancestry in the production of survival strategies and meaning building for existence in the midst of the fractured locus.